Evaluation of Facial Profile and Dental Caries Among Patients Attending Private Dental College in Chennai- Observational Study - SUSHANTHI, S.; RAJ, SS; BALASUBRAMANIAM, ARTHI (The journal of contemporary issues in business and government, 2021)
There are conflicting opinions about the contribution of malocclusion and facial forms to the development of dental caries. This study aims to determine the association between facial profile and dental caries among patients attending private dental college. A retrospective study was conducted using 4645 case records of patients attending private dental college from July 2019- March 2020 .Facial profile was estimated by lateral view of photographs taken during diagnostic examination. Dental caries were assessed using DMFT index(decayed, missing, filling) and count of decayed teeth(dt) alone separately taken for analysis. Data analysis was done. Descriptive statistics and chi-square association was done. About 74.45% of participants have straight profiles followed by 16.34% and 8.93% have convex and concave profile respectively. 48% have a medium score of DMFT(7-15) followed by 47.16% have a low score of DMFT(0-6). No statistically significant association between facial profile and dental caries (p = 0.170) on chi-square association was found. In conclusion, no relationship between facial profile and dental status is found among the patients attending private dental college in Chennai.